Effect of bank-specific and governance-specific variables on the productivity and profitability of banks. Issue 8 (14th November 2016) - Narwal, Karam Pal; Pathneja, Shweta
Abstract : Purpose: The purpose of this paper is to analyze the effect of bank-related variables and corporate governance-related variables on the productivity and profitability of public and private sector banks in India. Design/methodology/approach: The Malmquist productivity index is applied to determine the productivity of different banks. Further, return on average assets is used as profitability of banks. The regression analysis is further used to assess the effect of different bank-related and governance-related variables on performance of banks. Findings: Nearly all the bank-specific variables explain the productivity and profitability of banks but a weak relationship is observed between individual governance variables and performance variables. Two governance variables, i.e. board meetings and remuneration explicate the profitability of the public sector banks and only duality explains the profitability of the private sector banks. No significance is found between productivity and governance variables. Originality/value: The study addresses the embryonic issue of corporate governance in the banking sector. The uniqueness of the paper lies in that no study has evaluated the effect of these variables on productivity and profitability of banks simultaneously.